2021
DOI: 10.31219/osf.io/xyuas
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AYUSH-64 as an adjunct to Standard Care in mild to moderate COVID-19: An open-label randomized controlled trial in Chandigarh, India

Abstract: Background: There is limited evidence on the safety and efficacy of administering Ayurveda interventions as add-on to the standard care for COVID-19. Objective: To explore the therapeutic efficacy and safety of AYUSH-64 as an add-on to standard care in the management of mild to moderate stage COVID-19.Design, setting, participants and interventions: This was an open-label randomized controlled trial with 80 patients of mild to moderate stage COVID-19. Participants in the AYUSH-64 add-on group received two tabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Safety studies have confirmed its tolerance up to 500mg/kg body weight in rodents. A clinical trial conducted by the Ministry of AYUSH, India, and the Council of Scientific and Industrial Research, India, demonstrated its efficacy in managing mild to moderate COVID-19 patients, with a significant decrease in IL-6 levels [31,32,25]. In our study, we evaluated the effect of A-64 on the expression of inflammatory genes in the presence of TLR7/8 inducers (Figure 7).…”
Section: Effect Of the Pretreatment Of Cells With Ayush-64 (A-64) On ...mentioning
confidence: 99%
“…Safety studies have confirmed its tolerance up to 500mg/kg body weight in rodents. A clinical trial conducted by the Ministry of AYUSH, India, and the Council of Scientific and Industrial Research, India, demonstrated its efficacy in managing mild to moderate COVID-19 patients, with a significant decrease in IL-6 levels [31,32,25]. In our study, we evaluated the effect of A-64 on the expression of inflammatory genes in the presence of TLR7/8 inducers (Figure 7).…”
Section: Effect Of the Pretreatment Of Cells With Ayush-64 (A-64) On ...mentioning
confidence: 99%